Leprosy: clinical and immunopathological characteristics - Luis Alberto Ribeiro Froes Junior; Mirian Nacagami Sotto; Maria Angela Bianconcini Trindade (Sociedade Brasileira de Dermatologia, 2022)
Abstract Leprosy, a disease caused by Mycobacterium leprae, has polymorphic neurocutaneous manifestations strongly correlated with the host immune response. Peripheral neural damage can lead to sensory and motor losses, as well as deformities of the hands and feet. Both innate and acquired immune responses are involved, but the disease has been classically described along a Th1/Th2 spectrum, where the Th1 pole corresponds to the more limited presentations and the Th2 to the multibacillary ones. The aim of this review is to discuss this dichotomy in light of the current knowledge of the cytokines, T helper subpopulations, and regulatory T cells involved in each presentation of leprosy. The text will also address leprosy reactions related to increased inflammatory activity in both limited and multibacillary presentations, leading to exacerbation of chronic signs and symptoms and/or the development of new ones. Despite the efforts of many research groups around the world, there is no standardized serological test/biological marker for diagnosis so far, even in endemic areas, which could contribute to the eradication of leprosy.